WOMAN IN THE SHADOW OF MODERNIZATION - Shihabuddin, Aris (Kafa`ah: Journal of Gender Studies, 2024)
Stereotypes against women did not only emerge during the New Order but have been present since the colonial era with various forms of discrimination, such as racial issues and colonizers' lust. The view that women's validity strata are low continues to develop and persist into the modern era. Although women gained wider space in the reform era. This research aims to look at women in the trap of modernization caused by the colonial era and the new order. The research method used is descriptive-qualitative. The data collection technique is done with contrapuntal reading strategy. Data analysis is done as follows. First, read the literature in depth until a thorough understanding is obtained. Second, recording narratives and events about women in the colonial era and the new order era. Third, examining each problem using Edward Said's framework. Fourth, presenting the results of the analysis. The result of the research is that women experienced discrimination in the scope of society due to the stigma built during the colonial era and the new order. The existence of MPR Decree No. IV of 1999 did not change the stereotype of women not being separated from the mattress, well, and kitchen.